Pengaruh Pengalaman dan Proses Reviu Pada Pertimbangan Auditor Dalam Menilai Penyajian Laporan Keuangan Pemerintah (Studi Pada Inspektorat Daerah di Provinsi Bali) - Wayan, Simpen I; I, Suartana Wayan; Dewa, Wirama Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aims to obtain an empirical evidence of the influence of auditor experience and review on auditor ’s judgement in assessing the financial statement of local government. This has been an important issue because the role of local insprectorat auditor has not been effective in performing the review tasks . Using the field experiment with factorial design 2 x 2, this study examined 90 local insprectorat auditors in Bali Province . The collected data were analized using ANOVA to know the difference effect of experience and review and their interactions on audito r’s judgement . Th is study shows some empirical findings. Firstly, the experienced auditors can make better judgements. Secondly, auditors who doing the review can increase the quality of their judgements. Thirdly, the difference level of experience and the difference treatment in doing the review process affect the auditor ’ s judgments. However, there is no interaction effect between experience and review on auditors’ judgments.
Keywords: auditor’s judgment, experience, review process.